Regras de políticas monetária e fiscal no Brasil: Evidências empíricas de dominância monetária e dominância fiscal - Mário Jorge Cardoso de Mendonça; Tito Belchior Silva Moreira; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Based on the hypothesis that the rulers of monetary and fiscal policy in Brazil may have been submitted to different regimes, the present study applies Leeper model (1991; 2005) in order to identify the chronology of policy regimes regarding their active and passive character. The policy rules are estimated by the Markov Switching (MS) model in which the regimes are endogenously identified. The results obtained allow us to place that fiscal dominance occurred in 2010 and between 2013 and 2014 while monetary dominance happened in much of 2003 and during the period from 2005 to 2007. The model still seeks to explain why the rate of Inflation during 2015 remained on the rise even though the monetary policy imposed by Central Bank was active.
Keywords: E52; E58; E62; 330; active monetary policy; fiscal dominance; reaction function; regime change; Markov-Switching model